Detailed decompositions in generalized linear models - Boris Kaiser (University of Bern, Department of Economics, 2013)
We propose a new approach for performing detailed decompositions of average outcome differentials, which can be applied to all types of generalized linear models. A simulation exercise demonstrates that our method produces more convincing results than existing methods. An empirical application to the immigrant-native wage differential in Switzerland is presented.
Keywords: C10; C50; C51; J31; 330; Oaxaca-Blinder; Detailed Decomposition; Generalized Linear Models